2008
DOI: 10.1002/rcm.3426
|View full text |Cite
|
Sign up to set email alerts
|

Trace level determination of trichloroethylene in biological samples by headspace solid‐phase microextraction gas chromatography/negative chemical ionization mass spectrometry

Abstract: A gas chromatography/negative chemical ionization mass spectrometry (GC/NCIMS) method using headspace solid-phase microextraction (HS-SPME) was developed for the determination of trichloroethylene (TCE) in blood, liver, kidney, lung and brain. The method was optimized with respect to several parameters including extraction time, extraction temperature, desorption time and salt addition. The method showed good linearity over the range of 0.025-25 ng/mL in blood and 0.075-75 ng/g in tissues with correlation coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Sprague‐Dawley rats (n = 4) were gavaged with 1 mg/kg of TCE as an aqueous emulsion. Serial blood samples were collected and analyzed immediately for TCE using a previously developed method 47. Blood samples were then assayed for TCE metabolites using the presently reported derivatization SPME‐GC/MS method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprague‐Dawley rats (n = 4) were gavaged with 1 mg/kg of TCE as an aqueous emulsion. Serial blood samples were collected and analyzed immediately for TCE using a previously developed method 47. Blood samples were then assayed for TCE metabolites using the presently reported derivatization SPME‐GC/MS method.…”
Section: Resultsmentioning
confidence: 99%
“…Blood samples from each rat (n = 4) were taken 2, 5, 10, 15, 30, 60, 120, 240, 360 and 480 min post‐dosing. Blood samples were analyzed immediately for TCE determination using a method developed previously 47. The samples to be analyzed for TCE metabolites were stored at 4°C until they could be analyzed (within 5 days).…”
Section: Methodsmentioning
confidence: 99%
“…For lower doses (0.0001, 0.001, 0.01, 0.1, 1.0 mg/kg), the MS was operated in negative chemical ionization mode (Liu et al, 2008a). For higher doses (2.5 mg/kg), the MS was operated in positive electron ionization mode (Liu et al, 2008b …”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] The methods were applied to the analysis of TCE from blood and a variety of tissues. The results demonstrated that the kinetics of TCE in blood and the tissues liver, kidney, lung and brain were linear across dosing from 1 mg/kg to 0.0001 mg/kg, enabling improved cancer risk determination.…”
mentioning
confidence: 99%
“…Several methods have been published describing the use of SPME for the analysis of TCE in biological samples. [1][2][3][16][17][18][19] However, no method is available for the determination of TCE from adipose tissue.…”
mentioning
confidence: 99%